Design of nanoconfined MWNTs@NaTi2(PO4)3 coaxial cables with superior rate capability and long-cycle life for Na-ion batteries. (September 2016) - Pang, Gang; Yuan, Changzhou; Nie, Ping; Zhu, JiaJia; Zhang, Xiaogang; Li, Hongsen; Ding, Bing
Graphical abstract: A simple yet efficient solvothermal method along with post-annealing has been developed to fabricate MWNTs@NaTi2 (PO4 )3 coaxial nanocables with well-crystalline NaTi2 (PO4 )3 sheath uniformly coating on the core of MWNTs. Due to the unique structures, the electrode exhibits excellent electrochemical performance as promising anode materials for Na-ion batteries. Highlights: The MWNTs@NaTi2 (PO4 )3 coaxial cables have been elegantly designed through solvothermal strategy combined with following calcination. The NaTi2 (PO4 )3 nanoparticles with an average diameter of ∼ 25 nm are uniformly coated on the surface of MWNTs, forming a 1D core-shell architecture. The MWNTs@NaTi2 (PO4 )3 electrode exhibits high charge–discharge capacity, good rate performance and long cycle life. Abstract: NASCION-type NaTi2 (PO4 )3 (denoted as NTP) has been established well as a promising anode material for Na-ion batteries (NIBs) in view of striking structure advantages. Unfortunately, the excellent rate capability of NTP is seriously limited by its intrinsic modest electrical conductivity. In this work, an efficient solvothermal strategy combined with following calcination is purposefully developed to synthesize morphology-controlled one-dimensional (1D) coaxial nanocables consisting of highly conducting multi-walled carbon nanotubes (MWNTs) cores and well-crystalline NTP sheath (afterwards designed as MWNTs@NTP). When evaluated as an anode for non-aqueous NIBs, the unique MWNTs@NTP coaxial nanocables exhibit excellent Na-storage performance with high charge–discharge capacities, rate performance and long cycle life, much better than those for MWNTs/NTP mixture, originating from the optimum design and synergetic effect of rapid electron delivery, convenient Na + transport and large electrode/electrolyte contacting sur-/interfaces provided by the three-dimensional entangling coaxial nanonetworks.